Family Caregivers’ Preparations for Death: A Qualitative Analysis - Breen, Lauren; Aoun, Samar; O'Connor, Moira; Howting, D.; Halkett, Georgia (Elsevier, 2018)
© 2018 American Academy of Hospice and Palliative Medicine Context: Many family caregivers are not prepared for the death of their family member or friend. Palliative care services tend to emphasize the patients' preparation for death rather than caregivers' preparation for, or living after, death. Caregivers’ perspectives on anticipating and preparing for death are under-researched, despite preparation being associated with better bereavement outcomes. Objectives: The objective was to explore family caregivers’ preparations for death. Methods: A total of 16 family caregivers of people in receipt of palliative care participated in semi-structured, face-to-face interviews. Transcripts were coded and analyzed using grounded theory techniques. Results: Analysis yielded two overarching themes: Here and Now centered on the caregivers’ focus on the multidimensional and all-consuming nature of caregiving for someone who is near death. Negotiating the Here/After described the tension the caregivers faced in vacillating between focusing on the care during the illness trajectory (Here) and worries and plans for the future (After). Conclusion: This exploratory study is the first to focus solely on family caregivers’ experiences of preparing for a death. The caregivers described the complexities of trying to prepare while feeling overwhelmed with demands of caregiving throughout an unpredictable illness trajectory. The caregivers in the present study were cognitively prepared, some were behaviorally prepared, but emotional preparedness was challenging. Services should not assume that all family caregivers are well-prepared for the death. Caregivers would likely benefit from the assessment and promotion of their death preparedness.